Managing Opportunistic Consumer Returns in Retail Operations - Altug, Mehmet Sekip; Aydinliyim, Tolga; Jain, Aditya (Management Science, 2021)
Retailers use lenient return policies to stimulate demand and increase revenues, as such policies help customers assess uncertain product valuations at low (or no) return cost and yield higher equilibrium prices. However, generous refunds also yield unintended consequences such as opportunistic returns, which take place when customers intentionally rent a product for short-term use. Accounting for 11% of all product returns in the United States in 2017, opportunistic returns prompt retailers to seek tactics to address adverse revenue and cost implications. We consider two alternative proposals using a price- and refund-setting newsvendor framework with two customer types: honest returners and renters. The first proposal, targeted-refunds, uses retail analytics firms to distinguish renters from honest returners and implements return policies tailored for each segment. The second proposal, menu-of-refunds, presents customers multiple price-refund pairs and lets them self-select. We compare and contrast the optimal decisions and the profit implications of both proposals with respect to two benchmark settings: one without any renters and another proposal, uniform-refunds, wherein the retailer merely reoptimizes its decisions while acknowledging that renters exist. We characterize the conditions under which the menu-of-refunds proposal separates customer types and thus matching or exceeding the performance of the targeted-refunds proposal. Furthermore, we study several alternative model specifications to confirm that our main finding concerning the effectiveness of the menu-of-refunds proposal is robust. This paper was accepted by Vishal Gaur, operations management.